Relationship between TMJ Disc Morphology and Early Oral Mucosal Inflammatory Disorders - Marwat, Tehmina; Aziz, Gulshad; Hameed, Aisha; Niaz Khan, Asma; Haidar, Adeel; Sajid, Bushra (Journal of Neonatal Surgery, 2025)
Background: TMJ disorders and inflammatory disease of oral mucosa are common in dental practice, but can be assessed as distinct clinical entities. There is currently an increasing amount of evidence demonstrating that functional and structural changes in the TMJ could impact upon an inflammatory process in surrounding oral tissues, especially in the early stages. Methodology: An analytical study, which is cross-sectional, was performed among 72 participants who presented with the symptoms of TMJ and/or early oral mucosal inflammatory changes. All participants underwent clinical oral examination and systematic TMJ examination. TMJ disc morphology could be assessed with MRI with respect to sagittal oblique closed-mouth images. The disc morphology was divided into the normal biconcave, thickened and folded and deformed types. The relationship between disc morphology and inflammatory disorders of oral mucosa was determined through statistical analysis. Results: Over fifty percent of subjects showed early oral mucosal inflammation. TMJ disc morphology in individuals who had mucosal inflammatory lesions was much different in shape as compared to those of normal disc shape. Abnormal disc morphology and presence and severity of oral mucosal inflammation were found to have a statistically significant relationship. Conclusion: The results demonstrate that there is a significant correlation between TMJ disc morphological changes and early oral mucosal inflammatory disorders. Acknowledgment of this relationship may stimulate the more comprehensive diagnosis of patients with initial inflammatory oral lesions.